Translatio Studii as Literary Innovation: Marie de France's Fresne and the Cultural Authority of Translation. (2nd October 2022) - Angerer, Michael Lysander
ABSTRACT: Medieval translations can be a shaping force in emerging vernacular literatures, as Marie de France's Fresne and its Old Norse and Middle English translations demonstrate. While Sif Ríkharðsdóttir highlights that each version is adapted to its target literature, these texts also draw on the cultural authority of translatio studii to legitimize innovation. This article traces each text's influence using Itamar Even-Zohar's polysystem theory, having determined their position within the literary polysystem through textual and manuscript contexts. Each version constructs its own cultural authority to reshape the polysystem for different ideological purposes, thus producing texts that differ both from their source material and the norms of their target literatures. This is most apparent in their representations of courtliness: by invoking translatio studii, the Anglo-Norman Fresne establishes an exemplar of sincere interiority-based courtesy, whereas the Old Norse Eskia instrumentalizes French prestige to legitimize a performative ideal of courtliness in Norwegian literature. Conversely, the Middle English Lay le Freine uses translatio to reinvent its genre as the socially inclusive Middle English Breton lay, where courtliness is primarily a literary effect. Intervernacular translations therefore emerge as a key source of innovation in vernacular polysystems, pointing towards a new approach to comparative medieval literature.